DIVERSIFIKASI OLAHAN BUAH CABAI DALAM BENTUK TEPUNG CABAI PADA KELOMPOK TANI CABAI BESAR DI KECAMATAN CENRANA - Isnaini, Junyah Leli; Yusuf, Muhammad (Jurnal BALIRESO, 2018)
Anticipate the low price of chili. at the time of over production and avoid the occurrence ofdamage (rotten fruit quickly) and extend the shelf period and increase the added value of chili fruitin District Cenrana, which needs to be done is to look for alteratif diversification processed chilifruit, chili fruit not only sold in fresh fruit but need to be done processing on the fruit, for exampleprocessing chili into chili flour so that damage can be minimized and provide added value. Thepurpose of this activity is to train the chili farmers to make the chili powder. The method used isthe extension method and the demonstration of making chili powder, guidance and mentoring.Results achieved are Partners skilled in terms of cultivation of large organic chili with the use ofappropriate cultivation technology Partners know the importance of chili pepper diversificationduring over production.